AB0143 Identification of Aberrant Expression of 14-3-3 Zeta by Multiple-Quantitative Validation Methods in Patients with Rheumatoid Arthritis. (10th June 2014) - Hayashi, S.; Suzuki, K.; Yoshimoto, K.; Takeshita, M.; Kurasawa, T.; Kondo, T.; Tanino, M.; Takeuchi, T.
Abstract : Background: The 14-3-3 proteins family consists of biologically essential protein kinases with multiple functions, such as in cell proliferation, differentiation, and cell cycle and functional regulation. It is evolutionally conserved and consists of 7 isoforms. Dysregulation of human 14-3-3 has been reported in several diseases such as neurologic disorders and cancers. Although aberrant up-regulation of 14-3-3 eta has been recently discovered in synovial fluid and serum in patients with rheumatoid arthritis (RA), little is known about the role of other family proteins. More interestingly, recent research showed that these proteins, including 14-3-3 zeta (YWHAZ), are activation-induced cytidine deaminase binding factors that work as essential elements in immunoglobulin class-switch DNA recombination [1]. Objectives: To validate the presence of 14-3-3 zeta in blood and clarify its immuno-pathological role in RA Methods: Peripheral blood samples obtained from untreated or methotrexate-naïve active RA patients who met either the 1987 and/or 2010 classification criteria and healthy individuals (HI) were enrolled. Total RNA was purified and relative mRNA expression was measured by quantitative PCR. Protein expression in peripheral mononuclear cells (PBMC) was evaluated by Western blotting. Further, intracellular expression was analyzed in a subpopulation by flow cytometry, and serum protein levels were measured by ELISA. Statistical correlation of expression with clinical indicators were analyzed. Results: In whole blood, expression of 14-3-3 zeta mRNA in RA patients (n=30) was significantly (p=9.0E-07) up-regulated compared to HI (n=27). In PBMC also, Western blotting showed up-regulation of 14-3-3 zeta in RA patients (n=9), to a comparable degree to that of mRNA. On intracellular staining by flow cytometry in 41 RA patients and 13 HI, expression in whole blood from RA patients tended to be increased (average 1.7 times) in the percentage of positive cells (p=0.07). Interestingly, further subpopulation analysis showed a tendency to increased expression in CD20+ B cells only (p=0.07), but no increase in CD14+ or CD8+ cells. With regard to serum concentrations, the proportion of RA patients with a high concentration of 14-3-3 zeta (n=31) was higher than that of HI (n=13), while no correlation was seen with either titers of rheumatoid factors or anti-citrulinated antibodies, unlike the case with 14-3-3 eta. Conclusions: We established different quantitation methods for 14-3-3 zeta in peripheral blood. Analysis showed up-regulation of 14-3-3 zeta in RA patients compared with HI. Aberrant expression of 14-3-3 proteins family, including eta and zeta, may link to B cell abnormalities in RA. References: Zhenming Xu et.al. Nat Struct Mol Biol. 17(9):1124-35, 2010 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3949